2015
DOI: 10.1515/ntrev-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Bonding properties of thiolate-protected gold nanoclusters and structural analogs from X-ray absorption spectroscopy

Abstract: Abstract:Subnanometer, atomically precise thiolateprotected gold nanoclusters represent an important advancement in our understanding of thiolate-protected gold nanoparticles and thiolate-gold chemistry. Aside from being a link between larger gold nanoparticles and small gold complexes, gold nanoclusters exhibit extraordinary molecule-like optical, electronic, and physicochemical properties that are promising for next-generation imaging agents, sensing devices, or catalysts. The success in elucidating a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 79 publications
(185 reference statements)
2
33
0
1
Order By: Relevance
“…The intensity of this transition inversely varies with the occupancy of the valence states and was analyzed in relation to bulk silver metal (Ag 0 ) and the ionic salt silver acetate (Ag + ) references. 36 The area under the white-line transition was integrated from ±3 eV of the absorption edge and compared with the two reference materials. Linearly interpolating the integrated area from the spectrum of the cluster gave ~35% Ag 0 and ~65% Ag + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of this transition inversely varies with the occupancy of the valence states and was analyzed in relation to bulk silver metal (Ag 0 ) and the ionic salt silver acetate (Ag + ) references. 36 The area under the white-line transition was integrated from ±3 eV of the absorption edge and compared with the two reference materials. Linearly interpolating the integrated area from the spectrum of the cluster gave ~35% Ag 0 and ~65% Ag + .…”
Section: Resultsmentioning
confidence: 99%
“…Two, X-ray absorption spectroscopy studies revealed the cluster oxidation state and fundamental bonding interactions in the cluster/DNA complexes in the native aqueous environment. 36 The Ag L 3 -edge X-ray absorption near-edge spectra gauged the cluster charge via the occupancy of the valence electronic states of silver. The extended X-ray absorption fine-structure region of the Ag K-edge spectra revealed three scattering paths, and these were ascribed to silver-nucleobase and two types of silver–silver interactions.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue to the electron‐donating groups in gelatin, Au (I) as an intermediate reduced state of gold has been produced, with a further reduction to Au (0). The aggregation of Au (0) results in the formation of a metal core with Au (I) on the surface as the nanoclusters' shell as a typical structure described in literature . After 24 h of reaction, all Au (III) has been totally reduced to Au (I) and Au (0) (Figure a).…”
Section: Resultsmentioning
confidence: 61%
“…From the knowledge gained throughout the characterization of the different AuNCs' optical properties and XPS studies introduced in this research work, accompanied with knowledge from literature about the general structure of gold nanoclusters, simplified models for the nanoclusters have been proposed, as shown in Figure c. Aug, where nanoclusters are produced only using gelatin, is considered the parent formulation that is further modified to other formulations with different properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation